The Losses from Traffic Accidents and the Insurance Claims Based on the Public Protection of Traffic Injury Act: Case Study of Buntharik Hospital, Ubon Ratchathani - บุญจูง, น้องเล็ก; พุทธิผล, จารุวรรณ (Journal of Health Science of Thailand, 2021)
A cross-sectional survey on losses resulting from traffic accidents and claims on benefits as stipulated by the Public Protection of Traffic Injury Act was conducted using questionnaires and through a review of accident-related expense records. Data was collected from 250 patients admitted resulting from traffic accidents at Buntharik Hospital, Ubon Ratchathani Province during January - April 2004. It was revealed that 80.8 percent of traffic accidents affected men and 82.8 percent were motorcyclists. Numbers of injured persons without safety helmets or belts and those with illegal alcohol levels were as high as 92.8 and 42.4 percent respectively. Fifty percent of the cases were critically affected by nearly fatal accidents. In terms of insurance, 56.4 percent of the cases had been covered by insurance. Of those having insurance, 54.4 percent bought only the minimum required package. Nevertheless, the proportion of injured people who had insurance and claimed for reimbursement under the Public Protection of Traffic Injury Act was only 39.7 percent. The mean total expenses for hospital treatment was 2,437.48 baht (36-45,000 baht) while the average of reimbursement from insurance companies was 12,760.54 baht (290-90,000 baht). It was also shown that people injured at various levels of severity did not incur statistically different total expenses (p>0.05) but insurance companies reimbursed different amounts (p<0.01). However, their satisfactions to wards the Public Protection of Traffic Injury Act were at 89.3 percent.